Tanzania in pictures - Crofts, Marylee S.; Reuben, Joel.; Lerner Publications Company (Minneapolis : Lerner Publications Co., 1988)
An introduction to the geography, history, government, economy, culture, and people of the African country boasting that continent's highest mountain, deepest lake, and largest game reserve.
Rev. ed. of: Tanzania in pictures / by Joel Reuben and Howard Carstens. 1972.
Includes index.
Keywords: Tanzania; Tanzania